Phytochemical and Pharmacological Studies on the Genus Psoralea: A Mini Review - Li, Cong-Cong (Evid Based Complement Alternat Med, 2016)
The genus Psoralea, which belongs to the family Fabaceae, comprises ca. 130 species distributed all over the world, and some of the plants are used as folk medicine to treat various diseases. Psoralea corylifolia is a typical example, whose seeds have been widely used in many traditional Chinese medicine formulas for the treatment of various diseases such as leucoderma and other skin diseases, cardiovascular diseases, nephritis, osteoporosis, and cancer. So, the chemical and pharmacological studies on this genus were performed in the past decades. Here, we give a mini review on this genus about its phytochemical and pharmacological studies from 1910 to 2015.